The The Influence Of Creativity and Innovation on Competitive Excellence on CV Tory Catering Bandung (SMEs) - Ramayani Yusuf; Mira Veranita; Heny Hendrayati; Zein Bastian (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
This research aims to analyze the influence of creativity and product innovation on competitive excellence Tory Catering in Bandung. The research uses quantitative research methods with observation data collection techniques, interviews, questionnaires, library studies, and library reviews. Data analysis techniques using SPSS 16 use are data Normalization Test Analysis, Pearson Product Moment Correlation, Determination Coefficient, Correlation Analysis, and Multiple Linear Regression Analysis. From the results of the study conducted by the authors on CV Tory Catering to find out the influence between creativity and product innovation on competitive excellence, the authors conducted a survey of questionnaires distributed to consumers as many as 120 respondents with decent results use as many as 92 respondents. The results showed that multiple linear regression analyses showed a positive coefficient value of 0.655, indicating a positive influence between Creativity and Innovation on Competitive Excellence. Keywords: Creativity, Product Innovation and Competitive Excellence, SMEs